A Pilot Study of Self-assessment by Educational Psychologists of the Conditions and Deficits of their Professional Activities in an Inclusive School - E.V. Samsonova; A.Yu. Shemanov; S.V. Alekhina; Yu.A. Bystrova (Психолого-педагогические исследования)
The purpose of the pilot study was to identify problems, deficits and conditions for ensuring the readiness of educational psychologists for effective professional activities in psychological support of students with special educational needs and normatively developing children in an inclusive school. The research methods were self-assessment tools for readiness and ability for psychological and pedagogical support in inclusive education, developed on the basis of competency-based and activity-based approaches, which included 4 questionnaires: attitude towards inclusion, intention to implement inclusive practices, reflection of difficulties and self-efficacy in implementing inclusive practitioner The total sample size was 89 respondents, who were educational psychologists from inclusive schools with higher education from 5 regions of the Russian Federation. Responses to the questionnaire were collected remotely through the ‘Anketolog’ system. Descriptive statistics for the questionnaires (M±SD) were performed, the distribution of answers to the questionnaires was checked for normality using the Kolmogorov-Smirnov test and correlation analysis was carried out using Spearman. Based on the average scores for the answers, the rating of answers on the “Effectiveness” and “Difficulties” questionnaires was determined. Analysis of the results of responses to the statements of the questionnaires showed a moderate positive correlation between all questionnaires, except for the Difficulties Questionnaire, where there was a negative correlation, which corresponds to the results of previously conducted studies on similar questionnaires. Almost all respondents have a positive attitude towards inclusion and a positive self-assessment of their readiness and ability to implement psychological and pedagogical support for students with special educational needs. The attitude of educational psychologists to the difficulties of implementing inclusion in school, expressed by a value of 2.714, corresponds to the prevailing choice of answers on a Likert scale between “Undecided” (3 points) and “Rather disagree” (2 points), which mainly reflects respondents’ disagreement with the presence of difficulties in their work, including disagreement with the lack of support from school administrators. Thus, in conditions of support from schools, educational psychologists show a positive attitude towards inclusion and evaluate their effectiveness in supporting students at a high level.